(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The concept of ‘Karma’ is one of the most important concepts of the religious, ethical, cultural and philosophical thoughts of India. It is considered to be the foundation stone of entire Indian philosophical outlook. Etymologically, the term ‘karma’ is derived from Sanskrit ‘Kr’. It means to do something. Thus, karma literally means action of any kind done by human beings. And metaphysically, karma means which of our past actions were causes of our present states of affairs. Moral value is also associated with karma. It is also used to mean an imperceptible force that shapes the destiny of a living being. The criteria of karma is not a mechanical principle but a spiritual necessity. “Every act, every thought is weighted in the invisible but universal balance scales of justice. The day of judgment is not in some remote future but here and now and none can escape it.” [The Hindu View of Life S. Radhakrishnan, p. 73]. The accumulated result and the force arising from an act can be called karma. The view of karma as found in Indian philosophy presupposes that any karma is bound to produce some result positive or negative.